Plasma exosomal miR-122 regulates the efficacy of metformin via AMPK in type 2 diabetes and hepatocellular carcinoma - Hui Peng; Mei Hou; Zixin Wu; Jing Wang; Man Zhou; Xiangjin Zhuang; Jiayu Xing; Qianqian Tao; Long Huang; Fuhai Zhou; Shengming Zhang; Qiyu Feng; et al. (Heliyon, 2022)
Metformin is a drug that has been applied in clinical use for many years for the treatment of type 2 diabetes mellitus (T2DM). It achieves its function through multiple targets and modulation of multiple signaling pathways. To date, the mechanism of the action of metformin is still not fully understood. Along with glycemic control, metformin has shown good inhibitory effects on the development of many tumors. Here, we elucidated that plasma exosomal microRNA-122-5p (miR-122) is closely related to the mechanism of metformin. MiR-122 regulates glycogen-glucose metabolism in hepatocytes or hepatocellular carcinoma cells (HCC) by inhibiting the phosphorylation of AMPK. Since miR-122 and metformin regulate glucose metabolism homeostasis through similar mechanisms, miR-122 can antagonize the effects of metformin. MiR-122 expression increases the sensitivity of hepatocytes or HCC to metformin. Conversely, decreased expression of miR-122 results in hepatocyte insensitivity to metformin. Therefore, significantly elevated levels of miR-122 in plasma exosomes of hepatocellular carcinoma patients could enhance their sensitivity to metformin. The results of the present study revealed a key regulatory role of plasma exosomal miR-122 on the molecular mechanism of metformin. The regulation of key molecules of related signaling pathways by miR-122 may lead to similar glycemic lowering and tumor suppression therapeutic effects as metformin. This provides new ideas for the development of new therapeutic strategies for hepatocellular carcinoma based on the mechanism of miR-122 and metformin.